New Generation of Libraries Using Emerging Technologies: Focus and Action Plans towards User’s Satisfaction - Ramesh, L.S.R.C.V. (Journal of Information and Knowledge, 2008)
Phenomenal advancements have taken place in the field of information and communication technologies in the last decade. Spectacular and innovative changes are expected to take place in these fields in the coming decades. Networking technologies are going through a sea change. Impact of mobile communication on possible wireless libraries is brought out. Economic and social changes are bound to give a fillip to online or e-education using web based technologies. The need for correlation and comparison of data from distributed sources is giving rise to new discipline of virtual data warehousing, computer network technologies, online publishing, digital technology services, interoperability, RFID technology and consortia problems and technological resolutions are discussed. Finally, this paper highlights on focus and action plans to be employed to satisfy library users from time to time.